SPECIAL LABORATORY TESTING METHOD FOR EVALUATION PARTICLE BREAKAGE OF RAILWAY BALLAST MATERIAL - Fischer, S.; Németh, A. (Science and Transport Progress, 2018)
Purpose. There are special, standardized laboratory test methods to evaluate railway ballast particle breakage; they are the Los Angeles and the Micro-Deval abrasion test. The authors opine that these methods aren’t the most adequate methods to assess the real ballast particle degradation because in reality never occurs these kinds of stresses and strains (i.e. particles in a rotating drum with or without steel balls and with or without water). A new laboratory test procedure is needed. The authors attempted to configure an adequate one in 2014, it is detailed in the paper, as well as the initial results and improvement possibility. This test method is related to dynamic pulsating test, the particle size distributions (PSD) had to be determined before and after fatigue. In 2017-2018 the research is supported by ÚNKP-17-4 program. Methodology. Multi-level steel box is utilized with a special layer structure, detailed in the paper. Five different types of railway ballast samples were tested. PSDs were defined, and regarding to the results relationship between ballast particle degradation values (according to Los Angeles and Micro-Deval abrasion tests, as well as this newly developed laboratory test method) was searched, as well as time interval between necessity railway ballast cleaning work was also calculated. Findings. The authors sentenced the results regarding to the self-developed laboratory test method that is able to assess the particle degradation and time interval between railway ballast cleaning work more precisely related to the real railway operation circumstances. Relationship was determined between particle breakage according to standardized and unique (non-standardized) laboratory test methods. Originality. The paper summarized the results a newly developed laboratory test method for evaluation of the degradation of railway ballast particles. Practical value. It sentenced the possibility to improve the measurements and assessments regarding to the research phase supported by the ÚNKP-17-4 project.